Desempenho de preditores para o controle de filtro ativo em paralelo - Silva, Juan Pereira (2022)
This work presents different techniques for calculating predictors for the application of predictive control as a regulator system of an shunt active power filter (SAPF), which supplies distorted current grid. From that, some performance are analyzed for each presented method. Four discretization techniques were used: Euler’s Backward; trapezoidal; centered form and TSA (two-step ahead) The SAPF has the function of eliminating the current harmonic components present in the electrical grid by injecting currents, thus reducing distortions in the grid and improving the power factor of the installation. The mathematical modeling, discretization models , and the development of predictive control algorithm are discussed and presented in simulation using the Simulink/MATLAB platform. The validation of the system was presented and carried out through real-time simulations in the OP5700 simulator from OPAL-RT Technologies.